<span>This is the equation made from the problem where x=mystery number </span><span>2x+3(x+1)=4(x-1)</span><span>
</span><span>Now let's solve for x! </span><span> </span><span>We start by distributing 3 into (X+1) </span><span> </span><span>3(x)=3x and 3(1)=3 </span><span> </span><span>Now our equation is 2x+3x+3=4(x-1) </span><span> </span><span>Let's combine both x values on the left side of the equation: 2x + 3x=5x </span><span> </span><span>We now have 5x+3=4(x-1) </span><span> </span><span>Let's distribute 4 into (x-1) </span><span> </span><span>4(x)=4x and 4(-1)=-4 </span><span> </span><span>Now our equation is 5x+3=4x-4 </span><span> </span><span>subtract 3 form both sides </span><span> </span><span>5x=4x-7 </span><span> </span><span>subtract 4x from both sides </span><span> </span><span>x=-7 </span><span> </span><span>Yay! So the number she is thinking of is -7!</span><span>
The experimental probability can be represented as a fraction of the number of times a five was not the result over the total number of times the cube was rolled.